Islam dan Nasionalisme (Kajian Terhadap Pemikiran KH. Abd A’la) - Moh. Ainul Yaqin (JSP: Jurnal Studi Pesantren, 2023)
The term nationalism has always carried out two angles—both pros and cons. The affirmative group holds a belief that the ideas albeit come from the West, the values can still be adapted to Islamic values. On the other hand, the opposite considers that all Western ideas can damage the Islamic values and even take over the existing Islamic values. This research is intended to describe three things: First, what is the basic concept of Islam and nationalism? Second, how does Kiai Abd. A'la think about Islam and nationalism? Third, how is Kiai Abd. A'la's socio-academic construction of Islam and nationalism? This paper uses Karl Manheim's sociology of knowledge theory along with Peter L Barger's social reality theory with a naturalistic and interpretative form of qualitative research then presented using historical and biographical methods based on data obtained through documentation, interviews, and observations. Analysis of the existing data resulted in several conclusions: First, the basic concept of Islam rahmatan lil alamin upholds horizontal compassion, both towards fellow humans and the environment. Meanwhile, the basic concept of nationalism is love for the motherland, willing to risk body and soul to defend the sovereignty and unity of the Indonesian republic regardless of race, ethnicity and religion. Second, in a way that is based on Kiai Abd. A'la, nationalism was historically born because of colonialism. The concept of nationalism adopted and fought for in the archipelago is in accordance with Islamic values, even the nationalism of the former era up to this present day cannot be separated from Islam. Third, the social construction of kiai Abd A'la based on religious understanding and the NU organisation. Kiai Abd. A'la's construction goes through three stages, namely externalisation, objectivation, and internalisation.